La double séance La musique sur la scène théâtrale et littéraire / La musica sulla scena teatrale e letteraria - LANDI, Michela (Biblioteca di Studi di Filologia Moderna, 2017)
If the play, our device, had no other function than to project, "at some elevation", certain lacks of which we would hardly be aware, there can only be in the Letters, according to Mallarmé, a single essential act: to question the relationships that this device maintains with some internal state of ourselves. We believe, with the author of La Musique et les Lettres, that it is through the play of their often rival relationships that the arts can be understood and make us understand. This game, which never stops urging us, constantly asks us for new instruments for its implementation - or its staging.